PEMBERDAYAAN EKONOMI KREATIF PEDESAAN MELALUI PLASTIC WASTE RECYCLING (STUDI KASUS BANK SAMPAH MANDIRI DESA TEBING LINGGAHARA KEC. BILAH BARAT KAB. LABUHAN BATU) - Hasri Nasution; Hendra Harmain; Nurul Inayah (EKSYA : Jurnal Ekonomi Syariah, 2022)
The purpose of this study is to see: (1) The pattern of cooperation carried out in the independent waste bank, (2) the process carried out by the waste bank in empowering the creative economy of rural communities through plastic waste recycling at the Mandiri Desa Garbage Bank. Linggahara Cliff Kec. West Bar Kab. Labuhan Batu, (3) The social and economic impacts felt by the community from the presence of the Mandiri Waste Bank. This study uses a qualitative descriptive research approach. The qualitative approach is more directed to in-depth or detailed analysis (in-depth analysis), namely examining problems one by one because the characteristics in each problem are not the same as one another. The results obtained through this study are a creative economic empowerment process carried out through plastic waste recycling or plastic waste recycling in independent waste banks that has been carried out quite well. Plastic waste recycling activities carried out by the Mandiri Waste Bank have provided many impacts as well as social and economic benefits for the community and members.